3+2*A+B*4/2-4 = 3 + 2A + 2B - 4 = 2A + 2B - 1
A / 3 * 6 + 4^Nd = 2A + 4^Nd
a = 4
2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4
-2a + 5 = 1 -2a = -5 + 1 -2a = -4 a = -4/-2 a = 2
3+2*A+B*4/2-4 = 3 + 2A + 2B - 4 = 2A + 2B - 1
-4 + 10 + 6a - 2a + 3 9 + 4a
2a*3 = 8+4a 6a = 8+4a 6a-4a = 8 2a = 8 a = 4
A / 3 * 6 + 4^Nd = 2A + 4^Nd
(2a - 3)(3a - 4)
a = 4
2a + 3a + 4 = 5a + 4
2a*4b*(-3c) = ? 2 * 4 * -3 * a * b * c = ? -24abc
5a + 3 = 7a - 1 add 1 to both sides 5a + 4 = 7a so 4 = 2a as 5a + 2a = 7a 4 = 2a = 2 x 2 so a = 2 Check: then 5a + 3 = 10 + 3 = 13 and 7a - 1 = 14 - 1 = 13
2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4
7a + 4 = 5a + 7 7a = 5a + 3 2a = 3 a = 3/2
2a -3 means 2 times a minus 3 if a = 2 we have 2 x 2 - 3 = 4 - 3 = 1